Gender, Loneliness and Happiness during COVID-19 - Anthony Lepinteur; Andrew E. Clark; Ada Ferrer-i-Carbonell; Alan Piper; Carsten Schröder; Conchita D'Ambrosio (Institute of Labor Economics (IZA), 2022)
We analyse a measure of loneliness from a representative sample of German individuals interviewed in both 2017 and at the beginning of the COVID-19 pandemic in 2020. Both men and women felt lonelier during the COVID-19 pandemic than they did in 2017. The pandemic more than doubled the gender loneliness gap: women were lonelier than men in 2017, and the 2017-2020 rise in loneliness was far larger for women. This rise is mirrored in life-satisfaction scores. Men's life satisfaction changed only little between 2017 and 2020; yet that of women fell dramatically, and sufficiently so to produce a female penalty in life satisfaction. We estimate that almost all of this female penalty is explained by the disproportionate rise in loneliness for women during the COVID-19 pandemic.
Keywords: I10; I14; I18; I30; 330; COVID-19; loneliness; life satisfaction; gender; SOEP